Groundwater contamination through potentially harmful metals and its implications in groundwater management - Ullah, Zahid; Rashid, Abdur; Ghani, Junaid; Nawab, Javed; Zeng, Xian-Chun; Shah, Muddaser; Alrefaei, Abdulwahed Fahad; Kamel, Mohamed; Aleya, Lotfi; Abdel-Daim, Mohamed M.; Iqbal, Javed (Frontiers in Environmental Science, 2022)
Groundwater contamination through potentially harmful metals (PHMs) is an environmental hazard in Pakistan with significant human health risk reports. This research presents the values of pH, total dissolved solids (TDS), electrical conductivity (EC), and potentially harmful metals (PHMs) like arsenic (As), manganese (Mn), lead (Pb), zinc (Zn), copper (Cu), nickel (Ni), and iron (Fe), in 243 samples collected from community tube-wells of Sheikhupura, Pakistan. PHMs such as As (91%), Mn (14%), Pb (97%), Fe (45%), Zn (15%), in those samples were beyond the permitted limit recommended by the world health organization (WHO). Principal component analysis (PCA) results with total variability of (60%) reveal that the groundwater sources of the study area are contaminated due to (31%) geogenic sources, (31%) anthropogenic sources, and (38%) both geogenic and anthropogenic sources. Such sources may include rock-water interaction, mining actions, agricultural practices, domestic sewage, and industrial effluent in the study area. Saturation indices show that the aquifers of the study area are saturated with lead hydroxide, zinc hydroxide, and goethite minerals, indicating that these minerals have a vital role in the contamination of groundwater. Health risk assessment results predicted that the non-carcinogenic risk (HQ) values of PHMs were found within the permissible limit (<1), except As (1.58E+00) for children, while carcinogenic risk (CR) values of all selected PHMs were lower than the maximum threshold CR value (1×10-4).